Difference between revisions of "2023 AMC 10A Problems/Problem 11"
(→Solution 1) |
(→Solution) |
||
Line 24: | Line 24: | ||
<cmath>2x^2-2x\sqrt{3}+1=0</cmath>. | <cmath>2x^2-2x\sqrt{3}+1=0</cmath>. | ||
− | By the quadratic formula, we find <math>x=\frac{\sqrt{3}\pm1}{2}</math>. Hence, our answer is <math>\frac{\sqrt{3}-1}{\sqrt{3}+1 | + | By the quadratic formula, we find <math>x=\frac{\sqrt{3}\pm1}{2}</math>. Hence, our answer is <math>\frac{\sqrt{3}-1}{\sqrt{3}+1}=2-\sqrt{3}.</math> |
~SirAppel | ~SirAppel |
Revision as of 19:51, 9 November 2023
A square of area is inscribed in a square of area
, creating four congruent triangles, as shown below. What is the ratio of the shorter leg to the longer leg in the shaded right triangle?
[asy]
size(200);
defaultpen(linewidth(0.6pt)+fontsize(10pt));
real y = sqrt(3);
pair A,B,C,D,E,F,G,H;
A = (0,0);
B = (0,y);
C = (y,y);
D = (y,0);
E = ((y + 1)/2,y);
F = (y, (y - 1)/2);
G = ((y - 1)/2, 0);
H = (0,(y + 1)/2);
fill(H--B--E--cycle, gray);
draw(A--B--C--D--cycle);
draw(E--F--G--H--cycle);
[\asy]
Solution
Note that each side length is and
Let the shorter side of our triangle be
, thus the longer leg is
. Hence, by the Pythagorean Theorem, we have
.
By the quadratic formula, we find . Hence, our answer is
~SirAppel